Advanced catalyst for NH3 production - Zhao, Liang Er (Nanyang Technological University, 2020)
Ammonia (NH3) is one of the most globally produced chemical for industrial use. It is an important carbon-free energy carrier and also an important chemical for producing fertilizers. Ammonia is mainly synthesized by a traditional Haber–Bosch process with high energy consumption and large amounts of greenhouse gas emissions. Therefore, we need to come up with another route for achieving green and sustainable ammonia synthesis at ambient conditions. Electrochemical nitrogen reduction reaction (NRR) has been proposed as a promising method for ammonia production. However, the NRR process is strongly hindered by the competitive side reaction, hydrogen evolution reaction (HER) for many NRR catalysts. Therefore, the development of electrochemical nitrogen-to-ammonia conversion is still challenging due to the low ammonia yield and unsatisfactory Faradaic Efficiency (FE) mainly deriving from the poor catalytic activity of catalysts. In this project, we will focus on how to use advanced catalysts such as boron, antimony and boron-antimony to produce ammonia via the electrochemical NRR. First, we will discuss on how to synthesize the catalysts. Second, we will study the characterization of the synthesized catalysts’ samples using scanning electron microscope (SEM), X-ray diffraction (XRD) microscopy and ultraviolet-visible (UV-Vis) spectroscopy. Then, in the electrochemical test conducted, the synthesized samples were able to allow the adsorption of hydrogen and nitrogen. After which, we will tabulate the results of the ammonia yield and Faradaic efficiency under negative applied potentials of -0.3 V vs. the reversible hydrogen electrode (RHE) and -0.4 V vs. RHE for the individual synthesized samples. Based on the tabulated experimental results, it can be concluded that the synthesized samples have comparable, if not better, NRR performance as compared to the existing catalysts used to produce ammonia. Finally, we will end off with recommendations for future research to develop prospective catalysts that can be used in the electrochemical method for ammonia production.